Volume 6: Turbo Expo 2004 2004
DOI: 10.1115/gt2004-54337
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Advanced Microturbine System Using Humid Air Turbine Cycle

Abstract: A prototype machine for a next generation microturbine system applying a simple humid air turbine system (design target of electrical output: 150 kW, electrical efficiency: 35% LHV) was developed for its laboratory evaluation. A low NOx combustor which applied a lean-lean zone combustion concept and water lubricated bearings were developed for the prototype machine. Operation using two water lines for the humid air turbine (HAT) was proposed as an effective way to obtain rated electric output to ambient temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Dodo et al built a 150 kW e mHAT coupled with a Water Atomizing inlet air Cooling (WAC) line. Experiments resulted in dry stable operation at 32% electrical efficiency and reduced NO x emissions in the exhaust [12]. Thereafter, Nakano et al showed through water injection experiments that the combination of WAC and HAT eventuated in a 3% absolute efficiency increase [13].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Dodo et al built a 150 kW e mHAT coupled with a Water Atomizing inlet air Cooling (WAC) line. Experiments resulted in dry stable operation at 32% electrical efficiency and reduced NO x emissions in the exhaust [12]. Thereafter, Nakano et al showed through water injection experiments that the combination of WAC and HAT eventuated in a 3% absolute efficiency increase [13].…”
Section: Introductionmentioning
confidence: 96%
“…Several authors have investigated the beneficial effect of converting an mGT into an mHAT, both from a numerical and an experimental perspective [9][10][11][12][13][14][15]. Parente et al carried out a thermodynamic assessment of the mHAT cycle, concluding that an existing mGT can be operated as an mHAT without major re-design [9].…”
Section: Introductionmentioning
confidence: 99%
“…Different cycle configurations are presented in open literature, such as cascade HAT [3], externally fired HAT [4], part flow HAT [5], Advanced HAT (AHAT) [6] and micro HAT (mHAT) [7]. More recent theoretical investigations are presented in Refs.…”
Section: Introductionmentioning
confidence: 98%
“…Various advanced gas turbine cycles, such as combined cycle (CC), steam injection turbine (STIG) cycle and humid air turbine (HAT) cycle, have been proposed and studied. After initially patented by Rao [1] in 1989, HAT has been paid more attention due to its eminent performance of low grade heat recovery and many system configurations have been presented in open literatures [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%